Sartre's critique of Husserl. Issue 1 (2nd January 2020) - Webber, Jonathan
ABSTRACT: This paper articulates a new understanding of Sartre's philosophical methodology in his early publications up to and including Being and Nothingness . Through his critique of Husserl across these works, Sartre develops an original and sophisticated variety of transcendental phenomenology. He was attracted to Husserl's philosophy for its promise to establish the foundations of empirical psychology but ultimately concluded that it could not fulfil this promise. Through the analyses that led him to this conclusion, Sartre formulated a new kind of phenomenological reduction and a distinctive kind of transcendental argument to draw conclusions about mind-independent reality from phenomenological premises. His aims were to dissolve the traditional distinction between mind and world, to establish that the mind is accessible to empirical study, and to formulate the conceptual framework required to study the mind systematically. Sartre's philosophy of psychology, therefore, drove the philosophical development of the methodological foundation of his philosophical project.